2021
DOI: 10.3390/ijms22031308
|View full text |Cite
|
Sign up to set email alerts
|

The SARS-Coronavirus Infection Cycle: A Survey of Viral Membrane Proteins, Their Functional Interactions and Pathogenesis

Abstract: Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) is a novel epidemic strain of Betacoronavirus that is responsible for the current viral pandemic, coronavirus disease 2019 (COVID-19), a global health crisis. Other epidemic Betacoronaviruses include the 2003 SARS-CoV-1 and the 2009 Middle East Respiratory Syndrome Coronavirus (MERS-CoV), the genomes of which, particularly that of SARS-CoV-1, are similar to that of the 2019 SARS-CoV-2. In this extensive review, we document the most recent information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
68
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(95 citation statements)
references
References 409 publications
1
68
0
4
Order By: Relevance
“…In fact, similarly to other viruses, pathogenic aspects of SARS-CoV2 infection observed at cellular level include an abnormal synthesis and accumulation of viral proteins in the endoplasmic compartment during the earliest phases of virus replication [ 22 ]. SARS-CoV proteins, such as the E protein, may have a direct role in ER stress and in the apoptotic signaling of the infected cell, as well as in the release of the matured virus by the formation of the ER–Golgi intermediate compartment [ 41 , 42 ]. In our study, the ER stress response to SARS-CoV2 infection was demonstrated by PERK expression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, similarly to other viruses, pathogenic aspects of SARS-CoV2 infection observed at cellular level include an abnormal synthesis and accumulation of viral proteins in the endoplasmic compartment during the earliest phases of virus replication [ 22 ]. SARS-CoV proteins, such as the E protein, may have a direct role in ER stress and in the apoptotic signaling of the infected cell, as well as in the release of the matured virus by the formation of the ER–Golgi intermediate compartment [ 41 , 42 ]. In our study, the ER stress response to SARS-CoV2 infection was demonstrated by PERK expression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…1a ). In SARS-CoV-2-infected lung epithelial cells, the replication and transcription of the virus genome produces a high load of the E protein, which localizes to the ERGIC region for viral assembly and budding 12 . It is proposed that the specific interactions between E and PALS1 recruit PALS1 to the site of virus assembly, and could possibly disrupt the polarity complex and vascular structure 4 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been assumed that the early CD4 + and CD8 + response is protective, and if it is not inhibited after a while, the late response is excessive and destructive for the organism [ 21 , 22 ]. It is worth mentioning that the SARS-CoV-2 infection is divided into four phases, of which phase III is characterized by an abnormal inflammatory response, which is associated with systemic complications and extrapulmonary manifestation of the disease that led to phase IV infection, including acute respiratory distress syndrome (ARDS) and multi-organ failure [ 23 , 24 ]. In critically ill patients, a drastic decrease in T-lymphocytes has been noted [ 21 , 25 ].…”
Section: Immune Response To Sars-cov-2 Infection: Most Important Factsmentioning
confidence: 99%